Granice nauki o polityce jako dyscypliny naukowej (Politeja, 2015)
Borders of Political Science as a DisciplineThe paper discusses the area of Political Science as a discipline and its borders. The four chapters include: terminology and its practical consequences, genesis and development of Political Science, research methods of Political Science and the position of Political Science in comparison to Social and Human Sciences.